Characterization of GABAB Receptor in the Human Colon - Yasuhito Uezono; Muneshige Kaibara; Hideki Hayashi; Shunsuke Kawakami; Akihito Enjoji; Takashi Kanematsu; Kohtaro Taniyama (Elsevier, 2004)
Characterization of the GABAB receptor in the human colon was performed by the reverse transcription-polymerase chain reaction (RT-PCR). mRNAs for both subunits of the GABAB receptor, GABAB1 and GABAB2, were detected in the human colon. The GABAB1(e) isoform was detected in the human colon, but not in the brain, and the other isoforms, except GABAB1(d), were detected in both tissues. Thus, the GABAB receptor may be present as a heterodimer with subunits of GABAB1 and GABAB2 in the human colon. Keywords:: GABAB1 subunit, GABAB2 subunit, RT-PCR